Unveiling Fieldbus Network Technology through Project-based Learning - Lucena, Samuel E. de [UNESP]; Mogames, Omar [UNESP]; IEEE (Ieee, 2012)
Fieldbus communications networks are a fundamental part of modern industrial automation technique. This paperwork presents an application of project-based learning (PBL) paradigm to help electrical engineering students grasp the major concepts of fieldbus networks, while attending a one-term long, elective microcontroller course.
Keywords: Hands-on education; projec-based learning; automation; networks; fieldbuses; microcontrollers